Bandwidth enhancement for transimpedance amplifiers. - Analui, B. (IEEE Journal of solid state circuits)
A technique for bandwidth enhancement of a given amplifier is presented. Adding several interstage passive matching networks enables the control of transfer function and frequency response behavior. Parasitic capacitances of cascaded gain stages are isolated from each other and absorbed into passive networks. A simplified design procedure, using well-known low-pass filter component values, is introduced. To demonstrate the feasibility of the method, a CMOS transimpedance amplifier (TIA) is implemented in a 0.18-μm BiCMOS technology. It achieves 3 dB bandwidth of 9.2 GHz in the presence of a 0.5-pF photodiode capacitance. This corresponds to a bandwidth enhancement ratio of 2.4 over the amplifier without the additional passive networks. The transresistance gain is 54 dBΩ, while drawing 55 mA from a 2.5-V supply. The input sensitivity of the TIA is -18 dBm for a bit error rate of 10-12.